2003
DOI: 10.1093/emboj/cdg221
|View full text |Cite
|
Sign up to set email alerts
|

The integral membrane protein p16.7 organizes in vivophi29 DNA replication through interaction with both the terminal protein and ssDNA

Abstract: A.Serna-Rico and D.Mun Äoz-Espõ Ân contributed equally to this workRemarkably little is known about the in vivo organization of membrane-associated prokaryotic DNA replication or the proteins involved. We have studied this fundamental process using the Bacillus subtilis phage f29 as a model system. Previously, we demonstrated that the f29-encoded dimeric integral membrane protein p16.7 binds to ssDNA and is involved in the organization of membrane-associated f29 DNA replication. Here we demonstrate that p16.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Structural Basis for p16.7C Oligomerization-Recent studies have shown that p16.7 multimerization is a prominent feature in its DNA binding mode (11). Here we have demonstrated that p16.7C retains the capacity to form multimers, implying that the C-terminal half of p16.7 contains one or more regions responsible for p16.7C dimer-dimer interaction.…”
Section: The Functional Domain Of Protein P167 Can Form Multimers-gelmentioning
confidence: 59%
See 3 more Smart Citations
“…Structural Basis for p16.7C Oligomerization-Recent studies have shown that p16.7 multimerization is a prominent feature in its DNA binding mode (11). Here we have demonstrated that p16.7C retains the capacity to form multimers, implying that the C-terminal half of p16.7 contains one or more regions responsible for p16.7C dimer-dimer interaction.…”
Section: The Functional Domain Of Protein P167 Can Form Multimers-gelmentioning
confidence: 59%
“…First, it binds nonspecifically to both ss-and dsDNA (10 -12). Second, p16.7 can form multimers, both in vitro and in vivo, and it has been shown that multimerization is crucial for its DNA binding mode (11). Third, it has affinity for the 29 terminal protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunofluorescence studies showed that p16.7 is required for efficient spreading of 29 DNA replication from its initial to additional sites at the membrane of the infected cell (27). In vitro analyses of a soluble p16.7 derivative lacking the membrane anchor revealed that (i) it is a dimer with unspecific DNA binding activity, (ii) it has affinity for the 29 terminal protein, and (iii) it is able to form higher-order multimers upon DNA binding (36,37). The solution and crystal structures of the dimeric functional C-terminal half of p16.7, p16.7C (residues 63 to 130) (32), as well as the crystal structure of p16.7C complexed with double-stranded DNA have been recently solved (1,2).…”
mentioning
confidence: 99%